Schaum's outline of theory and problems of electronic devices and circuits - Cathey, Jimmie J. (Schaum's outline series, 1989)
This updated version of its internationally popular predecessor provides and introductory problem-solved text for understanding fundamental concepts of electronic devices, their design, and their circuitry. Providing an interface with Pspice, the most widely used program in electronics, new key features include a new chapter presenting the basics of switched mode power supplies, thirty-one new examples, and twenty-three PS solved problems.